충북지역 발생 논잡초 분포 조사 - 김은정(Eun Jeong Kim); 박재성(Jae Seong Park); 이채영(Chae Young Lee); 임상철(Sang Cheol Lim); 박인서(In Seo Park); 조용구(Yong Gu Cho) (Weed & turfgrass science, 2014)
The survey of weed occurrence was conducted to identify dominant weed species in the paddy field. Total 346 sites of the 12 regions in Chungbuk Province in Korea were investigated in July, 2013. Weed flora was composed of 43 species belonged to 15 families. The compositions of major plant families, Cyperaces, Poaceae, Pontederiaceae and Asteraceae, were 21.5, 17.4, 15.5 and 12.7%, respectively. Based on life cycle, weed species was grouped into annuals of 71.3 and perennials of 28.1%. The most dominant weed species in paddy fields of Chungbuk Province were Monochoria vaginalis (14.5%), followed by Scirpus juncoides (10.5%), Echinochloa oryzoides (9.3%), Eleocharis kuroguwai (7.0%), Aeschynomene indica (6.2%) et al. The similarity of paddy weeds in 12 regions observed through TWINSPAN analysis was distinguished by Persicaria longiseta, Aneilema keisak, Persicaria thunbergii, Fimbristylis millacea, Blyxa japonica, Digitaria ciliaris, Potamogeton distinctus, Cyperus nipponicus. This information could be useful for estimation of future weed occurrence and establishment of weed control methods in chungbuk province in Korea. 충북지역의 이앙재배 논의 잡초 분포 현황을 조사하기 위하여 2013년 충북지역 12개 시 군의 346지점에 대한 잡초 발행 분포를 조사한 결과를 요약하면 다음과 같다. 충북지역 논에 발생하는 잡초는 모두 15개과 43초종이었고 과별 우점도는 방동사니과 21.5%로 가장 높았고 그뒤로, 화본과 17.4%, 물옥잠과 15.5%, 국화과 12.7%순이었다. 충북지역에서는 1년생 잡초는 32초종, 다년생 초종이 11종 분포하였고, 발생비율은 일년생이 71.3%, 다년생이 28.1%로 일년생잡초 발생 비율이 높았다. 충북지역 우점잡초는 물달개비(14.5%), 올챙이고랭이(10.5%), 강피(9.3%), 올방개(7.0%), 자귀(6.2%), 순이었다. 그 외의 지역은 모두 물달개비가 가장 우점하는 초종으로 조사되었다. TWINSPAN 분석을 통한 시 군의 잡초 유사성 분석 결과 개여뀌, 사마귀풀, 고마리, 바람하늘지기, 올챙이솔, 바랭이, 가래, 나도방동사니가 시 군을 구별하는 지표종으로 영향을 미쳐 이 초종의 출현 유무에 따라 지역별 논 잡초 유사성을 비교할 수 있었다. 이러한 정보를 이용하여 충북지역 잡초발생을 예측하고, 이에 맞는 잡초 관리방안을 수립할 수 있을 것으로 판단된다.